Does Online Search Improve the Match Quality of New Hires? - Nicole Gürtzgen; Benjamin Lochner; Laura Pohlan; Gerard J. van den Berg (Institute of Labor Economics (IZA), 2021)
This paper studies the effects of the high-speed internet expansion on the match quality of new hires. We combine data on internet availability at the local level with German individual register and vacancy data. Results show that internet availability has no major impact on the stability of new matches and their wages. We confirm these findings using vacancy data, by explicitly comparing match outcomes of online and non-online recruits. Further results show that online recruiting not only raises the number of applicants and the share of unsuitable candidates per vacancy, but also induces employers to post more vacancies.
Keywords: J64; H40; L96; C26; 330; matching; internet; informational friction; recruiting channel; vacancy; wage; job duration